Growth and Fabrication of GaAs Thin-Film Solar Cells on a Si Substrate via Hetero Epitaxial Lift-Off - Woo, S.; Ryu, G.; Kim, T.; Hong, N.; Han, J.-H.; Chu, R.J.; Bae, J.; Kim, J.; Lee, I.-H.; Jung, D.; Choi, W.J. (MDPI, 2022)
We demonstrate, for the first time, GaAs thin film solar cells epitaxially grown on a Si substrate using a metal wafer bonding and epitaxial lift-off process. A relatively thin 2.1 ？m GaAs buffer layer was first grown on Si as a virtual substrate, and a threading dislocation density of 1.8 × 107 cm？2 was achieved via two In0.1Ga0.9As strained insertion layers and 6× thermal cycle annealing. An inverted p-on-n GaAs solar cell structure grown on the GaAs/Si virtual substrate showed homogenous photoluminescence peak intensities throughout the 2” wafer. We show a 10.6% efficient GaAs thin film solar cell without anti-reflection coatings and compare it to nominally identical upright structure solar cells grown on GaAs and Si. This work paves the way for large-scale and low-cost wafer-bonded III-V multi-junction solar cells. ？ 2022 by the authors. Licensee MDPI, Basel, Switzerland.